Alkyl amine functional dextran macromonomer‐based thin film composite loose nanofiltration membranes for separation of charged and neutral solutes. Issue 37 (28th May 2017) - Trivedi, Jaladhi S.; Bera, Anupam; Jewrajka, Suresh K.
ABSTRACT: Thin film composite (TFC) nanofiltration membranes with defined porous structure of the separation layer are desirable for the concentration of neutral solute and separation of salts from a mixture. Herein, we report the formation of TFC membranes composed of polyamide (PA) separation layer by the interfacial polymerization between new dextran‐butyl amine (Dex‐NH2 ) macromonomer and trimesoyl chloride on polysulfone support membrane. The membranes prepared with 1%–1.5% (wt/vol) of Dex‐NH2 exhibited water permeance of 110–116 L m −2  h −1  MPa −1 with 62%–71% rejection of Na2 SO4 and 12%–14% rejection of MgCl2 . The membranes also showed about 91% rejection of poly(ethylene glycol) of molecular weight 2000 g/mol and about 11% rejection of NaCl. A decrease in permeance and ions selectivity was observed with increasing concentration of Dex‐NH2 . The dextran chains attached to the PA network restrict the diffusion of Dex‐NH2 toward the interfacial zone and thereby assist the formation of porous and thin PA layer compared to that when free amine (alkyl diamine) was used. These membranes are applicable for the separation of small molecular weight neutral solutes from mixture containing monovalent salts. © 2017 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2017, 134, 45301. Abstract :